A comparative study of partial dealcoholisation versus early harvest: Effects on wine volatile and sensory profiles. (30th September 2018) - Longo, Rocco; Blackman, John W.; Antalick, Guillaume; Torley, Peter J.; Rogiers, Suzy Y.; Schmidtke, Leigh M.
Highlights: Wines were produced from early and late harvest grapes and dealcoholisation. A combined reverse osmosis-evaporative perstraction process was used. The concentration of many volatile compounds decreased during dealcoholisation. Dealcoholised wines were distinctively different from both early and late harvest wines. The ComDim approach was used for an overall evaluation of the results obtained. Abstract: Two Verdelho and Petit Verdot wines were produced from sequential harvests of grapes. The alcohol concentration of early harvest (EH) and late harvest (LH) wines were respectively 9% and 13.5% v/v for Verdelho, and 10.5% and 13% v/v for Petit Verdot. LH wines were dealcoholised to match the same alcohol level of EH samples using a combined reverse osmosis-evaporative perstraction process. In dealcoholised wines, there was a decrease in volatile compounds (esters particularly) compared to LH treatments. For both varieties, the sensory attribute ratings for overall aroma intensity and alcohol mouthfeel also decreased following dealcoholisation. Dealcoholised wines were distinctively different from both LH and EH wines even though these wines had similar alcohol level to EH wines. When dealcoholisation is considered for high-alcohol wines, it is important to consider that membrane effects can significantly change depending on the wine non-volatile matrix composition and the level of alcohol reduction required.